Disclosure Regulation, Corruption, and Investment: Evidence from Natural Resource Extraction - Thomas Rauter (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2019)
I examine how mandatory disclosure of fiscal payment information in developed countries affects fiscal revenue contributions and investments by multinational firms in less developed countries. In Europe and Canada, extractive firms have to publicly disclose their payments to foreign host governments in a granular report on their corporate website to discourage the bribery of foreign public officials and other illicit payment avoidance practices. Using data on firms' extractive activities abroad and exploiting the staggered adoption of extrac- tion payment reports across developed countries, I find that disclosing companies increase their payments to host governments and that public officials book a higher fraction of these payments into government ledgers, particularly in corrupt countries. However, the higher government revenue comes at a cost disclosing firms decrease and reallocate investments relative to non-disclosing competitors. Additional cross-sectional evidence indicates that the increased threat of public shaming and legal enforcement are two important mecha- nisms through which these disclosures generate real effects. Overall, my evidence suggests that extraction payment disclosures improve fiscal revenue collection but have unintended investment consequences for multinational firms.
Keywords: G14; G38; H20; H26; K22; L71; M41; M48; O10; 330; Real Effects; Disclosure Regulation; Corruption; Fiscal Revenues; Foreign Investment; Corporate Social Responsibility